Re-attendance to the emergency department. Issue 6 (22nd May 2008) - Whiticar, R; Webb, H; Smith, S
Abstract : The re-attendance of patients to emergency departments is becoming an increasingly common problem and yet there is not much research available on this subject. This report describes an audit carried out in the emergency department of this hospital, specifically looking at the issue of re-attendance and if there is anything that can be done to prevent it. Traditionally, emergency departments in the United Kingdom have been staffed at junior doctor level by senior house officers (SHO); however, with the advent of modernising medical careers in the United Kingdom, departments are being staffed at this level by foundation year 2 doctors (FY2). Whereas SHO range in experience from a year post-qualification to a possible 5–6 years post-qualification, all FY2 doctors have only one year post-qualification clinical experience. In this audit, FY2 doctors, despite seeing fewer patients per head than the middle-grade tier, had a higher level of re-attendance and it is hypothesised whether this is due to the impact of modernising medical careers on their training.